Faculty of geo - information science and earth observation :Powerpoint - Loran, T.M. (University of Twente, 2020)
This lecture presents: Faculty ITC - mission and mandate; Activities in Indonesia; Developments in cooperation; NGCBP : national geothermal capacity building program; GEOCAP : geothermal capacity building program; Trilateral collaboration.